2013
DOI: 10.7150/ijms.6104
|View full text |Cite
|
Sign up to set email alerts
|

Status of Essential Trace Minerals and Oxidative Stress in Viral Hepatitis C Patients with Nonalcoholic Fatty Liver Disease

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) may be an important factor leading to altered trace mineral homeostasis, thereby accelerating the progression of hepatitis C virus (HCV) infection. Our aim was to determine whether NAFLD influenced the status of certain essential trace minerals and oxidative stress in chronic HCV-infected patients.Design and Methods: Blood biochemical parameters were determined in a group of 30 healthy, non-obese, non-diabetic participants (CNL group), and hepatitis C patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 47 publications
5
40
0
1
Order By: Relevance
“…To our knowledge, this is the first study to compare the level of oxidative stress and anti-oxidative markers among patients with chronic hepatitis C virus infection versus nonalcoholic steatohepatitis. The main finding of our study proved excess level of oxidative and lower anti-oxidant markers in patients with NASH than patients with CHC and healthy volunteers, these results are in line with many previous studies (42,43).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…To our knowledge, this is the first study to compare the level of oxidative stress and anti-oxidative markers among patients with chronic hepatitis C virus infection versus nonalcoholic steatohepatitis. The main finding of our study proved excess level of oxidative and lower anti-oxidant markers in patients with NASH than patients with CHC and healthy volunteers, these results are in line with many previous studies (42,43).…”
Section: Resultssupporting
confidence: 81%
“…However, Patients with HCV and HCV-NAFLD groups had altered blood lipid profiles, higher IR, elevated liver enzyme activities, imbalances in anti-oxidant defense (42). To our knowledge, this is the first study to compare the level of oxidative stress and anti-oxidative markers among patients with chronic hepatitis C virus infection versus nonalcoholic steatohepatitis.…”
Section: Resultsmentioning
confidence: 94%
“…This decline is in agreement with published data that indicate the ability of zinc to modulate hepatic gene expression and lipid homeostasis [ 73 ]. Zinc finger transcription factors, peroxisome proliferation activator receptor- α (PPAR- α ) and hepatocyte nuclear factor-4 α (HNF-4 α ), play important roles in regulation of hepatic lipid metabolism [ 73 , 74 ]. However, excessive lipid accumulation in the liver is associated with the formation of ROS and release of proinflammatory cytokines [ 7 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the metabolism of carbohydrates and fats in humans is connected with zinc, copper and iron; and obesity's emergence could implicitly relate to disturbances in homeostasis [7]. For instance, several epidemiological studies have found a negative correlation between cellular zinc levels and the prevalence of obesity [8,9], whereas others have reported linkage between obesity and serum copper levels [10,11]. Abnormal cellular chromium, selenium, iron and other mineral concentrations have been reported in obese patients as well [12,13].…”
Section: Introductionmentioning
confidence: 99%